UTILIZATION OF INSTAGRAM REELS @biestro.indonesia AS A PROMOTIONAL MEDIA FOR BIESTRO BINJAI TOURISM (International Journal of Cultural and Social Science, 2026)
This study examines the utilization of Instagram Reels on the @biestro.indonesia account as a digital promotional medium for Biestro Binjai Tourism and analyzes how short-form video content constructs destination appeal, encourages audience engagement, and supports visitor decision-making. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation involving the social media administrator, management, and visitors of Biestro Binjai from January to March 2026. The data were analyzed using Robert Entman’s framing theory and the AIDA model (Attention, Interest, Desire, Action) to explain how promotional messages are constructed and how audiences respond to them. The findings show that Biestro’s Reels content is managed through weekly thematic planning, the use of strong opening hooks such as “free entrance and parking,” the framing of exclusive attractions, emotional moment capture, relevant music selection, creative captions, and internal quality control. The “real only” content policy also strengthens the consistency between digital representation and visitors’ actual experiences. The use of Instagram Reels indicates an expanded audience reach beyond Binjai, increased public interaction, and stronger visitor trust, particularly after viral and collaborative content. However, the effectiveness of Reels is also shaped by challenges such as the need for continuous content innovation, audience fatigue, repetitive questions, and comment management to maintain brand image. This study contributes to digital marketing communication by showing that Reels can function not only as a promotional tool, but also as a strategic medium for framing local tourism identity, building authenticity, and converting digital attention into actual tourist visits.